If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 12 + 4y = 32 Reorder the terms: 12 + 5x + 4y = 32 Solving 12 + 5x + 4y = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 5x + -12 + 4y = 32 + -12 Reorder the terms: 12 + -12 + 5x + 4y = 32 + -12 Combine like terms: 12 + -12 = 0 0 + 5x + 4y = 32 + -12 5x + 4y = 32 + -12 Combine like terms: 32 + -12 = 20 5x + 4y = 20 Add '-4y' to each side of the equation. 5x + 4y + -4y = 20 + -4y Combine like terms: 4y + -4y = 0 5x + 0 = 20 + -4y 5x = 20 + -4y Divide each side by '5'. x = 4 + -0.8y Simplifying x = 4 + -0.8y
| 8-2x=-26 | | -15+x=-8 | | 4+5n=8n+7 | | 5/6x(x-3)-10(x-3) | | 3x/-0.5=1.9 | | F(x)=x^3-x+1 | | 48m^2-3x^2=0 | | n/2-4 | | 3(4z-1)-2(z+1)=3(z+1) | | -4(8v-1)=32-4v | | 5(x+2)=4(x-2)+x | | -2r-5=2r+4 | | 5(x+4)-(4x-7)=4 | | x+2x+5=26 | | -7(6a-6)-3a=222 | | -2y+2(-6-4)=9+2(1-y) | | 2=(10=z)/-3 | | 1000c^3+27=0 | | y=X^3+3X^2-45X | | 2(x-6)-(5x+3)=4(6x+3) | | x+2x+5=27 | | 125a^3-8b^3=0 | | 55/31=x/12 | | (-5-x)(1-x)(5-x)=0 | | 10-4(3x-1(1-x))= | | -25+25x+x^2-x^3=0 | | -6x+6(-x-4)=-96 | | 5.21x-6.09=2.77x+9.83 | | 64x^2-144xy+81y^2=0 | | 5(5x-3)+1=5x | | 10-(x-3)=12 | | 2t-1=8-t |